2009
DOI: 10.1086/597270
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Cycling and Mechanism of Physical Dormancy Break in Seeds ofIpomoea hederacea(Convolvulaceae)

Abstract: Sensitivity cycling to physical dormancy (PY) break in seeds is known to occur in some Fabaceae and Convolvulaceae species. PY in seeds of species of Convolvulaceae and of some other angiosperm plant families can he broken by storing them dry. However, the mechanism of opening the warer gap In the seed coat (dormancy break) during dry storage has not been investigated. In research reported here, we determined whether sensitivity cycling occurs in seeds of Ipomoea hederacea (Convolvulaceae) and investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…The requirement for wet-high temperatures to break PY in S . multijuga seeds and the relationship between seed traits of this species support the role of internal pressure in the PY-breaking mechanism in seeds proposed by Jayasuriya et al [ 25 , 29 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The requirement for wet-high temperatures to break PY in S . multijuga seeds and the relationship between seed traits of this species support the role of internal pressure in the PY-breaking mechanism in seeds proposed by Jayasuriya et al [ 25 , 29 ].…”
Section: Discussionsupporting
confidence: 82%
“…This relation is true in the case of physically dormant seeds that need moisture to break dormancy. The role of internal pressure in breaking PY was hypothesized by Jayasuriya et al [ 25 , 29 ], who observed a distinct response to wet and dry conditions for seeds of congeneric species of Convolvulaceae to become permeable. Similarities are shared by S .…”
Section: Discussionmentioning
confidence: 99%
“…Jayasuriya et al . (,b, ,b) interpreted these two steps for breaking PY as changes between insensitive and sensitive stages (sensitivity cycling) and reported the effect of moisture on this process. Sensitivity cycling has been reported only in seeds of Fabaceae and Convolvulaceae and only in herbaceous species of these two families (see Jayasuriya et al .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the ability to remain ungerminated can result from either an innate dormancy mechanism or the absence of conditions conducive to radicle protrusion (Thompson 2000). Burial conditions in this investigation were previously determined to be conducive to radicle protrusion for both velvetleaf and ivyleaf morningglory (Baloch et al 2001;Jayasuriya et al 2009). Thus, seeds categorized as persistent were also dormant.…”
Section: Methodsmentioning
confidence: 85%